2007
DOI: 10.1093/jjco/hyl127
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcome of Stage III and IV Adrenocortical Carcinoma

Abstract: Resection for stage III, IV ACCs affords the possibility of negative margins, acceptable peri-operative morbidity and mortality, and prolongs survival in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…However, because up to 10% of adrenocortical carcinomas and 49% of metastasis can occur bilaterally [2,16,17] and sometimes cause adrenal insufficiency [18], an accurate differentiation between tuberculosis and malignancy may be radiologically and clinically difficult without surgical confirmation. Moreover, as in our case, the presence of adjacent organ invasion at the preoperative CT might increase suspicion of adrenal malignancy [5,16].…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…However, because up to 10% of adrenocortical carcinomas and 49% of metastasis can occur bilaterally [2,16,17] and sometimes cause adrenal insufficiency [18], an accurate differentiation between tuberculosis and malignancy may be radiologically and clinically difficult without surgical confirmation. Moreover, as in our case, the presence of adjacent organ invasion at the preoperative CT might increase suspicion of adrenal malignancy [5,16].…”
Section: Discussionsupporting
confidence: 47%
“…When these typical radiologic and clinical manifestations occur together, the correct diagnosis of adrenal tuberculosis is likely. However, in adrenal tuberculosis, the direct invasion to adjacent organs has not been reported but is instead suggestive of advanced stage of adrenal malignancy [5].…”
Section: Discussionmentioning
confidence: 99%
“…5 Owada et al reported liver resection in 6 patients as 4 segmentectomies and 2 extended right hepatectomies. 14 All had R0 resections. In our series, 27 patients with ACC metastatic to the liver underwent 19 liver resections and 8 RFA procedures (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…4,8,13 Resection of liver metastases has been reported, but most series are small or combine resections of other distant sites. 5,14,15 …”
mentioning
confidence: 99%
“…Surgery is considered to be the only method to cure ACC of in the early stage [7,8,9,10]. There were 15 cases of ACC in stages I and II in total.…”
Section: Discussionmentioning
confidence: 99%